Incidenza di patologie neoplastiche nei lavoratori del complesso petrolchimico di Porto Torres, 1990-2006 / Cancer incidence among petrochemical workers in the Porto Torres industrial area, 1990-2006 - Budroni, M.; Sechi, O.; Cesaraccio et al., R. (La Medicina del Lavoro, 2011)
Diversi studi hanno rilevato aumenti del rischio per alcune sedi neoplastiche tra i lavoratori dell’industria petrolchimica.  Abbiamo pertanto condotto il follow-up dell’incidenza di neoplasie in una coorte di  5350 lavoratori di sesso maschile dell’industria petrolchimica di Porto Torres (Sassari). Il follow-up ha interessato il periodo dal 01/01/1990, anno di accertata completezza della coorte e di inizio della disponibilità di tassi di riferimento prodotti dal Registro Tumori della provincia di Sassari, al 31/12/2006. Per sedi neoplastiche selezionate, abbiamo calcolato il rapporto standardizzato d’incidenza (sir), come rapporto tra eventi osservati ed attesi, ed il rispettivo intervallo di confidenza (IC) al 95%, nella coorte totale ed in sotto-coorti con potenziale esposizione ad agenti chimici valutati nelle monografie IARC. Nella coorte totale, è stato osservato un modesto aumento dell’incidenza neoplastica (596 casi; sir=1,09; IC 95% 1,00-1,18), ed in particolare dei linfomi non Hodgkin (NHL, 26 casi; sir=1,78; IC 95% 1,22-2,62), che sono risultati più elevati nei soggetti con anzianità lavorativa superiore a 10 anni e con una latenza superiore a 20 anni, e nella sotto-coorte degli addetti alla produzione e polimerizzazione del cloruro di vinile (VCM) (tutte le neoplasie, 51 casi; sir=1,43; IC 95% 1,08-1,88, NHL, 4 casi: sir=4,06; IC 95% 1,64-10,0). I nostri risultati suggeriscono che alcune esposizioni nell’industria petrolchimica, ed in particolare quella a VCM, potrebbero contribuire ad aumentare il rischio di neoplasie, e particolarmente di emolinfopatie maligne. Cancer incidence among petrochemical workers in the Porto Torres industrial area, 1990-2006Background: Various epidemiological  studies explored cancer mortality and incidence among petrochemical workers. We followed up cancer incidence in a cohort of 5350 male petrochemical workers in the industrial area of Porto Torres (Sardinia, Italy). Material and Methods: The follow-up covered the period from 01/01/1990, when completeness of the cohort was certain and reference rates by the local Cancer Registry became available, up to 31/12/2006. Cohort members were subjects employed for six months or more in one of the chemical plants of the industrial  area, alive as at 01/01/1990. Overall, a total of 81,392 person-years at risk were accumulated. The standardized incidence ratio (sir), as the ratio of observed to expected events, and its 95% confidence interval (CI) were calculated for all cancers and selected cancer sites, in the total cohort and in sub-cohorts of workers in plants where exposure to chemical agents evaluated in the IARC Monographs might have occurred. Results: An increase in risk for all cancers was observed in the total cohort (596 cases; sir=1.09; 95% CI 1.00-1.18), and it was highest for non-Hodgkin lymphoma (NHL, 26 cases: sir=1.78; 95% CI 1.22-2.62). Risk for haemo-lymphatic cancer was highest in the sub-cohort of workers employed for 10 years or more, with a latency period of 20 years or longer, and among those employed in the manufacture and polymerization of vinyl chloride (VCM; all cancers, 51 cases: sir=1.43; 95% CI 1.08-1.88; NHL, 4 cases: sir=4.06; 95% CI 1.64-10.0). Risk of haemolymphatic cancer was not significantly elevated in the sub-cohort potentially exposed to benzene. An excess risk of bladder cancer (RR=1.46; 95% CI 1.09-1.96), but not of pleural cancer, was observed in the sub-cohort potentially exposed to asbestos. No significant increase in cancer risk was observed among workers potentially exposed to acrylonitrile, butadiene, or styrene. Conclusions: Our follow-up study of petrochemical workers showed an increase in risk for all cancers, and particularly NHL, apparently concentrated among workers potentially exposed to VCM.